Islet amyloidosis in a child with type 1 diabetes. Issue 2 (4th March 2019) - Beery, Maria L.; Jacobsen, Laura M.; Atkinson, Mark A.; Butler, Alexandra E; Campbell-Thompson, Martha
ABSTRACT: Histopathology based studies of the pancreas obtained from organ donors are increasing our awareness of islet phenotypic heterogeneity during development and aging, as well as in settings of type 1 diabetes, type 2 diabetes, monogenic diabetes or other forms of this metabolic disease. Islet amyloidosis represents a histopathological feature classically ascribed to patients with type 2 diabetes. Herein, the occurrence of islet amyloidosis and its severity are reported in a child with type 1 diabetes along with histological comparisons of islet amyloidosis in two young adults with recent-onset type 1 diabetes. Islet amyloidosis was infrequent yet widely distributed throughout the pancreas in the child with type 1 diabetes and both adults with type 1 diabetes, with no such pathology seen in matched control donors. Analysis of these cases add to the increasing appreciation of islet heterogeneity in children and young adults with type 1 diabetes. Such knowledge also supports a notion that multiple pathophysiological mechanisms underlie the loss of functional β-cell mass in the spectrum of clinical phenotypes in patients with type 1 diabetes.